Assessment of the Selection and Acquisition Criteria of Information Resources In Federal University of Technology Akure Library - Omonori, Omonori; Adedayo, Abayomi; Olusegun, Adebambo Hameed (Journal of Advanced Research in Business and Management Studies, 2020)
The prevalent situation of inadequate funding of University libraries in Nigeria has posed great challenges for library/information resource centers to satisfy the target audience in the area of selection and acquisition of information resources. Selection is the act of deciding what information resources are added to the library collection and in what quantity while acquisition deals with locating and acquiring the information resources identified as appropriate for the collection. This study assessed the selection and acquisition criteria of information resources in Federal University of Technology Akure (FUTA) library. The study employed a quantitative approach conducted in a cross-sectional design. A total of 97 survey questionnaires was distributed out of which 72 questionnaires were returned indicating 74.2% response rate. The data collected was analyzed using descriptive statistics (mean) and the study revealed that contemporary significance or permanent value, format and ease of use as well as popular interest were highly rated methods of selection of information resources while purchases, gifts/donation and exchanges were highly rated methods of acquisition of information resources. Identified challenges include government fiscal policy, high foreign exchange, financial mismanagement by the academic administrators and library managers as well as inarticulate selection and acquisition development policy. The study recommended that contingency plans should be provided to mitigate against price fluctuations as a result of government fiscal measures and exorbitant foreign exchange. Library managers should possess basic financial knowledge and periodic training and development should be organized for library professionals to develop articulate selection and acquisition development policy.